Metastatic Cutaneous Involvement of Granulomatous Colitis in Hermansky‐Pudlak Syndrome. Issue 6 (4th April 2012) - Weitz, Nicole; Patel, Vishal; Tlougan, Brook; Mencin, Ali; Kadenhe‐Chiweshe, Angela; Morel, Kimberly D.; Lauren, Christine
<x xml:space="preserve">Abstract</x> Abstract: Hermansky‐Pudlak syndrome (HPS) is a rare autosomal‐recessive disorder characterized by oculocutaneous albinism, a hemorrhagic diathesis due to platelet dysfunction, and lysosomal ceroid accumulation that can cause a Crohn's‐like granulomatous colitis and pulmonary fibrosis. We report peristomal and vulvar cutaneous involvement of the granulomatous colitis in HPS.